THE NEEDS ANALYSIS OF SENIOR HIGH SCHOOL AT ARRAHMANIYAH DEPOK - Muhammad Faishol Nurul Huda (STKIP Persada Khatulistiwa Sintang, 2020)
This investigate inspected the interface of senior high school understudies in coordination English educating and learning, centering on the target needs and learning needs. The questionnaire consisting of parts A and B was administered to 46 MA Arrahmaniyah Depok students.. Portion A bargains with the target needs centered on the learner’s necessities, needs and needs of the learner that are successfully working within the target circumstance. On the other hand, Portion B concerns the learning needs that envelop learning inputs, methods, instructor and learner parts and settings. On the other hand, interviews were too conducted with the understudy and the English educator to gather information in arrange to analyze in-depth results of the encounter of educating English and to identify possible regions of dialect troubles for understudies to memorize English. The comes about proposed that the understudies have diverse recognitions of their necessities, wants, and lacks. The results also illustrated the learning needs of students, including learning inputs, teaching learning procedures, the role of teachers and learners, as well as teaching learning environments.